Spiritual Well-Being in People Living with Persistent Non-Cancer and Cancer-Related Pain. Issue 6 (9th December 2020) - Lovell, Melanie; Corbett, Mandy; Dong, Skye; Siddall, Philip
Abstract: Context: Existential and spiritual factors are known to play an important role in how people cope with disability and life-threatening illnesses such as cancer. However, comparatively little is known about the impact of pain on factors such as meaning and purpose in one's life and their potential roles in coping with pain. Objectives: The aim of this study was to determine spiritual well-being scores in people with persistent pain and to compare these with people with cancer and healthy controls. Methods: We assessed 132 people with chronic pain, 74 people with cancer (49 with pain and 25 without pain) and 68 control participants using standardised measures of pain-related variables including pain intensity, physical function, mood and cognitions. Spiritual well-being was also assessed using a validated and widely used questionnaire, the Functional Assessment of Chronic Illness Therapy – Spirituality Scale (FACIT-Sp). Results: Spiritual well-being scores were significantly lower in people with persistent pain when compared with controls and were no different when compared with people with cancer, including those who had cancer and pain. In addition, low levels of meaning and purpose were significant predictors of depression, anxiety, and stress across all groups. Conclusion: The findings demonstrate that persistent pain is associated with spiritual distress that is equal to those observed in people who have cancer. Furthermore, those who have higher levels of meaning and purpose are less likely to develop mood dysfunction when experiencing pain, indicating they may have a protective role.